(untitled) (CIPEEX, 2026)
Introduction: The SARS-CoV-2 pandemic began in 2020 and was responsible for a public health crisis of infection, primarily affecting the human respiratory system. Given this exceptional situation with limited therapeutic knowledge, empirical measures were taken. Among the protocols used experimentally, the use of antibiotics stood out; despite showing promising in vitro results, they did not prove to have an antiviral effect. Furthermore, the indiscriminate use of this therapeutic measure can lead to increased bacterial resistance. ​Objective: To analyze the diagnostic shift (COVID-19, Influenza, and Others) between the pandemic and post-pandemic periods. ​Method: This is a descriptive, retrospective study based on the collection of information regarding medication treatment from the medical records of patients hospitalized at Hospital Evangélico Goiano with suspected respiratory syndrome. ​Results: The study found a change in the diagnostic profile, with a statistically significant alteration in diagnostic hypotheses (p=0.0006). The predominant diagnosis was COVID-19 (80.8% - 101 patients vs 58.7% - 74 patients). ​Conclusion: In summary, there was a significant change between the analyzed period and the diagnostic hypothesis.